Infective Endocarditis Complicated by Severe Mitral Regurgitation and Markedly Elevated Troponin Levels as A Prognostic Marker: A Case Report - Dahir OF; Hassan MO; Adan AS; Abdi AE; Abdi IA (Research Reports in Clinical Cardiology)
Osman Farah Dahir, Mohamed Omar Hassan, Ahmed Shafie Adan, Ahmed Elmi Abdi, Ishak Ahmed Abdi Cardiology Department, Mogadishu Somali-Türkiye Training and Research Hospital, Mogadishu, SomaliaCorrespondence: Osman Farah Dahir, Department of Cardiology, Mogadishu Somali Türkiye Training and Research Hospital, Second Street, Black Sea, Hodan District, Mogadishu, Somalia, Tel +252618439596, Email bajiinfarah@gmail.comBackground: Infective endocarditis (IE) is a potentially life-threatening infection of the heart valves, often caused by bacterial pathogens. It can lead to serious complications such as heart failure, embolic events, and myocardial injury. Troponins, cardiac biomarkers released from damaged myocardial cells, are frequently elevated in IE, particularly in cases with myocardial injury. Elevated troponin levels in IE may serve as a prognostic marker of adverse outcomes, including mortality.Case Presentation: A 20-year-old male with no significant medical history presented to the emergency department with chest pain that had progressively worsened over the past week. On examination, the patient was stable, with a pan-systolic murmur at the apex, indicative of severe mitral regurgitation (MR). Laboratory tests revealed elevated troponin levels (5.553 ng/mL), and blood cultures returned positive for Staphylococcus aureus. A transthoracic echocardiogram and transesophageal echocardiogram (TEE) confirmed severe MR with large vegetation on the mitral valve. Despite starting a two-week course of intravenous antibiotics, the patient’s condition persisted, with elevated troponin levels (8.6 ng/mL) and ongoing vegetation. Mitral valve surgery was performed due to the failure of medical therapy and the risk of further myocardial injury.Discussion: This case underscores the critical role of elevated troponin levels as a prognostic marker for myocardial injury in infective endocarditis. Persistent troponin elevation, despite appropriate antibiotic treatment, indicates ongoing myocardial injury and suggests the need for urgent surgical intervention. Severe MR in IE contributes to hemodynamic instability and increases the risk of heart failure, necessitating prompt surgical correction. The collaboration between cardiologists, infectious disease specialists, and cardiac surgeons is vital in managing such complex cases.Conclusion: Elevated troponin levels in infective endocarditis, particularly with severe mitral regurgitation, are indicative of significant myocardial injury and may predict adverse outcomes. Timely surgical intervention is crucial to improving patient survival and mitigating further complications.Keywords: infective endocarditis, mitral regurgitation, troponin levels and prognostic marker